Genetic Analysis for Yield Components and Yield in Rice (Oryza sativa L.) - Chaturvedi, H. P.; Talukdar, P. (International Journal of Bio-resource and Stress Management, 2010)
Component analysis indicated importance of both additive and dominance gene action for the characters days to 50% flowering, 50% flowering to maturity, plant height, panicle length, grain filling percentage and length-breadth ratio, while only the dominance component was important for the characters like effective tillers per plant, panicle weight, grains panicle-1, 1000 grains weight and yield plant-1. Dominant genes were more frequent in the parents than the recessive genes for the characters days to 50% flowering, 50% flowering to maturity, plant height, panicle length and length-breadth ratio. Unequal gene frequencies for positive and negative alleles in the parents were observed for all the haracters except grains panicle-1 for which equal gene frequencies were evident. The estimates of degree of dominance were more than unity for all the characters including yield plant-1, which indicated prevalence of over-dominance.